2012
DOI: 10.1111/j.1365-2133.2012.10907.x
|View full text |Cite
|
Sign up to set email alerts
|

A new concept of a multidisciplinary lymphoedema centre: established in connection to a department of dermatology and the Copenhagen Wound Healing Center

Abstract: A multidisciplinary lymphoedema centre improves management, knowledge and awareness of lymphoedema. This model, with minor adjustments, may be applicable for other regions and countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 17 publications
(20 reference statements)
0
14
0
Order By: Relevance
“…The portal of entry is usually clear (leg ulcer, wound, excoriated leg dermatosis, toe web intertrigo, cracked plantar hyperkeratosis). For the upper limb, no similar study is available, but almost one‐third of women with breast cancer‐related lymphoedema developed cellulitis, 12 similar to LLL 13 …”
Section: Discussionmentioning
confidence: 99%
“…The portal of entry is usually clear (leg ulcer, wound, excoriated leg dermatosis, toe web intertrigo, cracked plantar hyperkeratosis). For the upper limb, no similar study is available, but almost one‐third of women with breast cancer‐related lymphoedema developed cellulitis, 12 similar to LLL 13 …”
Section: Discussionmentioning
confidence: 99%
“…Initially 30 subjects were included in the study: 10 healthy controls, 10 patients with confirmed diagnosis of lipoedema and 10 patients with confirmed diagnosis of lymphoedema. Patients were recruited from the Lymphoedema Center outpatient clinic at the Copenhagen Wound Healing Center, Bispebjerg University Hospital, Copenhagen . Only women were included, as lipoedema affects women almost exclusively.…”
Section: Methodsmentioning
confidence: 99%
“…4 It has been reported that 10-20% of patients referred to lymphoedema clinics are subsequently diagnosed with lipoedema. 5,6 Lipoedema and lymphoedema can be differentiated on medical history and clinical findings. However, it is often difficult to distinguish the two conditions, even for skilled practitioners, and lipoedema is frequently misdiagnosed as lymphoedema.…”
Section: What Does This Study Add?mentioning
confidence: 99%
See 1 more Smart Citation
“…Wound problems commonly occur in clinical practice; ∼l% of the global population suffers from persistent wound problems, and 5% of total medical costs are spent on wound treatments (1,2). Accurate wound treatment is required to solve this problem effectively, and such treatment relies on a better understanding of the wound healing mechanism.…”
Section: Introductionmentioning
confidence: 99%